PHYSICAL FUNCTION IN MIDLIFE AND OLDER ADULTS FROM AN AFRICAN AMERICAN CHURCH-BASED HEALTH SCREENING - Lange-Maia, B (Innov Aging, 2018)
Physical function (PF) limitations are associated with poor health outcomes. Though traditionally studied in older adults, the prevalence of PF limitations appears to be rising among midlife adults, particularly among disadvantaged populations. This study aimed to: 1) determine the prevalence of PF limitations among adults age 40+ who participated in church health screenings in underserved African American neighborhoods and, 2) assess correlates of PF limitations among midlife and older adults, particularly health conditions. PF was assessed using the Short Physical Performance Battery (SPPB). Demographics, smoking, health status/conditions, general physical activity, and neighborhood walking conditions were assessed via questionnaire, and body mass index calculated using objectively measured height and weight. Factors related to PF limitations (SPPB ≤9) were determined using logistic regression, with age stratified models used to determine whether factors differed between midlife (age 40–59) and older (age 60+) adults. In total, 731 participants completed the SPPB with data on comorbid health conditions (age 58.6 ± 10.3 years, 42% age 60+, 58% women, 97% African American). PF limitations were common (38%) and more prevalent among older adults (26% midlife, 56% older p<0.001). Adjusting for age, factors related to PF limitations included: fair/poor health (OR=1.92, 95% CI 1.34–2.76), stroke/neurologic issues (OR=3.78, 95% CI 2.03–7.03), and arthritis (OR=1.66, 95% CI 1.16–2.36). Participants reporting that they would enjoy walking in their neighborhood were less likely to have PF limitations (OR=0.66, 95% CI 0.46–0.96). Predictors of functional limitations were largely consistent in age stratified models. Programs focused on improving PF in expanded age groups are warranted.